Prevalence of rheumatoid cachexia in rheumatoid arthritis: a systematic review and meta‐analysis. Issue 5 (21st August 2018) - Santo, Rafaela C.E.; Fernandes, Kevin Z.; Lora, Priscila S.; Filippin, Lidiane I.; Xavier, Ricardo M.
Abstract: Background: Low muscle mass occurs in patients with rheumatoid arthritis without weight loss; this condition is referred as rheumatoid cachexia. The aim of the current study was to perform a systematic review with meta‐analysis to determine the rheumatoid cachexia prevalence. Methods: A systematic review with meta‐analysis of observational studies published in English, between 1994 and 2016, was conducted using MEDLINE (via PubMed) and other relevant sources. Search strategies were based on pre‐defined keywords and medical subject headings. The methodological quality of included studies was assessed using the Newcastle‐Ottawa Scale. Meta‐analysis was used to estimate the prevalence, and because studies reported different methods and criteria to estimate body composition and prevalence of rheumatoid cachexia, subgroup analyses were performed. Meta‐regression adjusted for the 28‐joint disease activity score and disease duration (years) was performed (significance level at P ≤ 0.05). Results: Of 136 full articles (one duplicate publication) screened for inclusion in the study, eight were included. The estimated overall prevalence of rheumatoid cachexia was 19% [95% confidence interval (CI) 07–33%]. This prevalence was 29% (95% CI 15–46%) when body composition was measured by dual‐energy X‐ray absorptiometry. When the diagnostic criteria were fat‐free mass index below the 10th percentile and fat mass index above the 25th percentile, rheumatoid cachexia prevalence was 32% (95% CI 14–52%). The 28‐joint disease activity score and disease duration had no influence on the estimated prevalence of rheumatoid cachexia ( P > 0.05). Most studies were rated as having moderate methodological quality. Conclusions: Meta‐analysis showed a prevalence of rheumatoid cachexia of 15‐32%, according to different criteria, demonstrating that this condition is a frequent comorbidity of rheumatoid arthritis. To better understand its clinical impact, more studies using standardized definitions and prospective evaluations are urgently needed.